Preparation method and application of iron-copper beta-cyclodextrin polymeric material for efficiently activating H2O2

The β-cyclodextrin polymer formed by cross-linking citric acid and β-cyclodextrin is combined with iron-copper bimetals to prepare iron-copper β-cyclodextrin polymer material for catalyzing the degradation of sulfonamide antibiotics, solving the problem of insufficient efficiency and circulation of existing catalysts and achieving efficient and environmentally friendly catalytic degradation effects.

CN119823398AInactive Publication Date: 2025-04-15GUILIN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411873701.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When degrading sulfonamide antibiotics, existing Fenton-like catalysts have problems with low reduction rate of high valence metals, low utilization rate of H2O2, and metal spillover and reuse.

Method used

A water-insoluble β-cyclodextrin polymer formed by cross-linking citric acid and β-cyclodextrin, combined with the iron-copper bimetallic catalytic activity center, was prepared for catalytic activation of H2O2 degradation of sulfonamide antibiotics.

Benefits of technology

This material exhibits excellent degradation performance of sulfonamide antibiotics in the Fenton-like system, has good reusability, low metal overflow rate and strong adaptability to environmental water bodies, and solves the efficiency and circulation problems of traditional catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823398A_ABST
    Figure CN119823398A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a novel heterogeneous Fenton-like catalytic material, i.e., a water-insoluble beta-cyclodextrin polymer is formed by esterification, polycondensation and crosslinking of citric acid and beta-cyclodextrin, and is combined with an iron-copper bimetallic catalytic active center through a metal coordination effect; a novel iron-copper beta-cyclodextrin polymeric material is successfully prepared and is used for catalyzing and activating H2O2 oxidized sulfonamide antibiotics SAs. Under the conditions that the temperature is 35 DEG C, the pH value is 3, the adding amount of the iron-copper beta-cyclodextrin polymeric material is 1.2 g / L, the adding amount of H2O2 is 10 mM, and the rotating speed of a stirrer is 500 r / min, the removal capacity of the iron-copper beta-cyclodextrin polymeric material Fenton-like system to 1 mg / L sulfameracil (SMR) is close to 90% within 10 min. The method provided by the invention has the characteristics of low cost, good effect, no generation of a large amount of iron mud, environmental protection and the like, is helpful for promoting the development of beta-cyclodextrin in the field of Fenton-like environment treatment, and provides an effective reference and a new thought for treatment of sulfonamide antibiotics in a water environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resource utilization and water treatment, and specifically relates to a method for preparing a complex metal iron-copper beta-cyclodextrin polymer material, and is used for catalyzing Fenton-like degradation of sulfonamide antibiotics in water. Background Art

[0002] Sulfonamide antibiotics (SAs) have spread into the water environment due to widespread abuse and incomplete treatment by existing processes, posing a threat to ecological safety and human health. Therefore, the prevention and control of SAs pollution in the water environment has always attracted the attention of researchers. Among the many methods for removing SAs-contaminated water bodies, the heterogeneous Fenton-like method has attracted attention due to its high activity, high efficiency and green environmental protection. It has the potential to replace the traditional homogeneous Fenton oxidation method and has become a popular technology in recent years. The mechanism of the heterogeneous Fenton-like method mainly involves the redox reaction between the metal center on the catalyst surface and H2O2, but there are still limitations such as low reduction rate of high-valent metals and low utilization rate of H2O2. Therefore, the performance requirements of Fenton-like catalysts are relatively high. Iron is the most commonly used Fenton starter, but the rate of Fe(Ⅲ)→Fe(Ⅱ) is slow, resulting in a large amount of iron sludge, which increases the treatment cost. The synergistic effect of the iron-copper bimetallic formed by the addition of copper ions can effectively activate H2O2 to produce ·OH, accelerate the electron transfer rate, and promote the reduction of high-valent metals, thereby greatly improving the performance of the catalyst. However, direct use of the iron-copper bimetallic material presents problems of metal spillage and recycling.

[0003] Cyclodextrin (CD) is a general term for a series of cyclic oligosaccharides produced by starch under the action of glucosyltransferase (produced by Bacillus). Commonly used cyclodextrins are usually molecules containing 6, 7, and 8 glucose units, which are called α-, β-, and γ-cyclodextrin, respectively. Since the cavity of α-CD is too small and the production cost of γ-CD is too high, β-CD is the cyclodextrin with the widest application range and the most research value due to its low cost, non-toxicity, tastelessness, and strong complexing ability. Each glucose that constitutes the β-cyclodextrin molecule is a chair-type conformation, and the glycosidic bonds in it cannot rotate freely, which makes cyclodextrin a geometrically stable conical ring structure with a rigid cavity and 21 hydroxyl groups. On the periphery of β-cyclodextrin, the wide end of the ring is composed of secondary hydroxyl groups (C2 and C3), and the other end is composed of primary hydroxyl groups (C6). The hydrophilic group makes the periphery of β-cyclodextrin significantly hydrophilic. The internal cavity of β-cyclodextrin is composed of non-polar C3 and C5 hydrogen atoms and glycosidic bond atoms. Since the CH bond has a strong shielding ability, the β-cyclodextrin cavity is hydrophobic. Therefore, the β-cyclodextrin molecule has a unique property of "hydrophilic outside and hydrophobic inside". Since the cavity can capture and encapsulate guest molecules like a cage, this host-guest encapsulation relationship allows the guest to enter a "microscopic heterogeneous environment", and then the structural characteristics and reaction performance of the guest molecule can be regulated by hydrogen bonds, van der Waals forces and steric hindrance. β-cyclodextrin can also improve the reaction efficiency by shortening the distance between the guest and the catalytic active center bonded to the cyclodextrin.

[0004] The cavity structure of β-cyclodextrin (β-CD) not only gives it a unique host-guest inclusion capacity, but also effectively improves the reaction rate of guest molecules. Studies have shown that cyclodextrin has great potential in improving the performance of Fenton-like catalysts. Therefore, it is envisaged to combine β-cyclodextrin with catalytic active centers to construct an efficient Fenton catalytic system for catalytic degradation of sulfonamide antibiotics SAs by H2O2. However, the water solubility of β-cyclodextrin limits its recycling as an efficient catalyst in the aqueous phase. The water-insoluble β-cyclodextrin polymer produced by citric acid cross-linking β-cyclodextrin is not only green and friendly, but also effectively solves the problem of water solubility. At present, this β-cyclodextrin polymer has been widely used as an adsorbent with high efficiency for heavy metals, organic pollutants, endocrine disruptors, etc. However, its application in the field of advanced catalytic oxidation has been rarely reported. Based on this, the present invention proposes a novel heterogeneous Fenton-like catalyst concept, which is to use citric acid and β-cyclodextrin to cross-link into a water-insoluble β-cyclodextrin polymer, combined with an iron-copper bimetallic catalytic active center, for catalytic activation of H2O2 to degrade SAs. The present invention has the advantages of low cost, green environmental protection, high efficiency, and recyclability, which helps to promote the application of β-cyclodextrin in the field of Fenton-like oxidation, and provides a certain theoretical basis for Fenton-like degradation of SAs-contaminated water bodies. Summary of the invention

[0005] In the field of Fenton-like catalysis, the research on citric acid cross-linked β-cyclodextrin polymers is very limited. Based on this situation, the present invention proposes a novel method for preparing a heterogeneous Fenton-like catalyst, that is, using citric acid and β-cyclodextrin to form a water-insoluble β-cyclodextrin polymer by esterification and polycondensation cross-linking, and combining the iron-copper bimetallic catalytic active center through metal coordination, successfully preparing a novel iron-copper β-cyclodextrin polymer material for catalytic activation of H2O2 to degrade sulfonamide antibiotics SAs. The optimal conditions for the material to be used as a Fenton-like catalyst to degrade sulfonamide antibiotics SAs (with sulfadiazine SMR as a representative pollutant) were obtained through condition optimization. The material exhibits excellent SAs degradation efficiency in the Fenton-like system, and has the advantages of good reusability, low metal overflow rate and strong adaptability to environmental water bodies. The system breaks through the problems of difficult recovery of traditional Fenton reagents and the generation of a large amount of iron sludge, and shows great potential in the treatment of trace organic water.

[0006] The specific steps are:

[0007] 1. Preparation of Fenton-like catalyst: Weigh 2.00 g of β-cyclodextrin and 1.00 g of monohydrated citric acid (mβ-CD: mCA = 2: 1) and add them to a 500 mL beaker, and add 1.50 g of potassium dihydrogen phosphate and 135.00 mL of ultrapure water to the beaker and mix well. Place the beaker in a 90 °C water bath stirring pot and stir for 15 min. After stirring for 5 min, add 3.00 g of ferrous sulfate and 1.00 g of copper nitrate (mFeSO4: mCu(NO3)2 = 3: 1), and continue stirring for 10 min. When the substances in the mixed solution are completely dissolved and the solution is clear and not turbid, seal the beaker with experimental tin foil, transfer the beaker to a digital display forced air drying oven at 135~145 °C for 3.5~4.5 h to obtain a brown solid product, take it out and cool it to room temperature, filter it with 500 mL of ultrapure water several times to remove impurities, and simmer at 60 The mixture was dried in a vacuum drying oven at ℃ for 12 h, taken out, and ground into the desired iron-copper β-cyclodextrin polymer material, recorded as CACD-Fe-Cu, which was placed in a desiccator for storage for future use.

[0008] 2. Prepare pollutant solution: Accurately weigh 0.10 g of SMR solid powder, dissolve it with a small amount of chromatographic grade methanol, and dilute it to 100 mL in a brown volumetric flask with ultrapure water to obtain an SMR stock solution with a concentration of 1000.00 mg / L. Store it at a constant temperature of 4 ℃ and away from light. Take a certain amount of SMR stock solution and ultrapure water and add it to a 250 mL beaker to make its concentration reach the set value. If there is no special instruction, the initial concentration of SMR is set to 1.00 mg / L.

[0009] 3. In a 250 mL beaker, accurately add a certain amount of the β-cyclodextrin polymer material obtained in claim 1 as a Fenton-like catalyst (0.20, 0.60, 1.20, 1.60, 2.00 g / L) and H2O2 (5.00, 10.00.00, 15.00, 20.00, 30.00, 40.00 mM), and control the total volume of the reaction liquid to be 50.00 mL. Use nitric acid and ammonia water to adjust the initial pH value of the solution (3, 4, 5, 6, 7, 8), wherein the amount of nitric acid and ammonia water does not exceed 0.5% of the total volume of the water sample. Then put the beaker into a digital constant temperature magnetic stirrer for reaction, turn on the digital constant temperature magnetic stirrer in advance, and adjust the temperature (25, 35, 45 ° C) and the speed (300, 500, 700 r / min). The time point when H2O2 was added into the reaction system was taken as the timing zero point. When the set sampling time (5 min, 10 min, 15 min, 20 min, 25 min, 30 min) was reached, 1 mL of sample was taken from the reaction solution with a disposable syringe sampler, passed through a 0.22 μm nylon membrane, and placed in a 2 mL brown injection bottle to which 0.50 mL of methanol had been added in advance. Methanol is a commonly used quencher for quenching hydroxyl radicals. The purpose of efficiently activating H2O2 with β-cyclodextrin polymer materials to generate hydroxyl radicals to degrade SMR was achieved.

[0010] The invention has the advantages of low cost, green environmental protection, high efficiency, and recyclability, etc., which helps to promote the application of β-cyclodextrin in the field of Fenton-like oxidation and provides a certain theoretical basis for Fenton-like degradation of SAs-polluted water bodies. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 These are scanning electron microscope examination images of the product of the present invention (SEM, a: ×10K; b: ×10K; c: ×10K; d: EDS).

[0012] Figure 2 This is the specific surface area diagram (BET) of the product of the present invention.

[0013] Figure 3 This is the infrared spectrum (FT-IR) of the product of the present invention.

[0014] Figure 4 This is the X-ray diffraction analysis spectrum (XRD) of the product of the present invention.

[0015] Figure 5 This is a graph showing the change in SMR degradation performance under different system conditions of the present invention.

[0016] Figure 6 This is a graph showing the change in SMR degradation performance of the product under different pH conditions of the present invention.

[0017] Figure 7 This is a graph showing the change in SMR degradation performance of the product under different dosage conditions of the present invention.

[0018] Figure 8 This is a graph showing the change in SMR degradation performance of the product under different H2O2 dosage conditions of the present invention.

[0019] Fig. 9 This is a graph showing the change in SMR degradation performance of the product under different temperature conditions of the present invention.

[0020] Fig.10 This is a graph showing the change in SMR degradation performance of the product under different rotation speed conditions of the present invention.

[0021] Fig.11 This is a diagram showing the change in SMR degradation performance of the product under different H2O2 addition conditions of the present invention. DETAILED DESCRIPTION

[0022] Embodiment 1:

[0023] 1. Preparation of iron-copper β-cyclodextrin polymer materials:

[0024] Weigh 2.00 g of β-cyclodextrin and 1.00 g of monohydrated citric acid (mβ-CD:mCA=2:1) ​​and add them to a 500 mL beaker, and add 1.50 g of potassium dihydrogen phosphate and 135 mL of ultrapure water to the beaker and mix well. Place the beaker in a 90 °C water bath stirring pot and stir for 15 min. After stirring for 5 min, add 3.00 g of ferrous sulfate and 1.00 g of copper nitrate (mFeSO4:mCu(NO3)2=3:1), and continue stirring for 10 min. When the substances in the mixed solution are completely dissolved and the solution is clear and not turbid, seal the beaker with experimental tin foil, transfer the beaker to a digital display forced air drying oven at 135~145 °C and react for 3.5~4.5 h to obtain a brown solid product. Take it out and cool it to room temperature, filter it with 500 mL of ultrapure water several times to remove impurities, and dry it in a 60 °C vacuum drying oven for 12 h. Take it out and grind it to obtain the desired iron-copper β-cyclodextrin polymer material, recorded as CACD-Fe-Cu, which is placed in a desiccator for storage for future use.

[0025] The phase and structure, component composition and morphology characteristics of the iron-copper β-cyclodextrin polymer material before and after the reaction were observed and tested by scanning electron microscopy (SEM / EDS), specific surface area analysis (BET), Fourier transform infrared spectrometer (FT-IR) and X-ray diffraction analysis (XRD).

[0026] 2. Preparation of pollutant stock solution sulfamethazine SMR:

[0027] Accurately weigh 0.10 g of SMR solid powder, dissolve it with a small amount of chromatography-grade methanol, and make up to volume with ultrapure water in a 100 mL brown volumetric flask to obtain an SMR stock solution with a concentration of 1000 mg / L. Store it at a constant temperature of 4 °C and avoid light for later use.

[0028] 3. Influence of different systems on Fenton degradation SMR performance:

[0029] (1) Take a certain amount of SMR stock solution and ultrapure water and add them into a 250 mL beaker to make the concentration reach the set value. Unless otherwise specified, the initial concentration of SMR is set to 1 mg / L;

[0030] (2) Using nitric acid and ammonia water to adjust the pH value of the treated liquid to 3 respectively;

[0031] (3) In a 250 mL beaker, the initial concentration of SMR was controlled to be 1 mg / L, the dosage of different system catalysts (β-cyclodextrin polymer, copper β-cyclodextrin polymer, iron copper β-cyclodextrin polymer, traditional Fenton reagent FeSO4) was 1.20 g / L, the dosage of H2O2 was 40.00 mM, and the total reaction volume was controlled to be 50 mL. The reaction was placed on a digital constant temperature magnetic stirrer at a temperature of 25 °C and a speed of about 500 r / min. The H2O2 addition time was used as the timing zero point, and samples were taken at 5 min, 10 min, 15 min, 20 min, 25 min, and 30 min respectively;

[0032] (4) Use a disposable syringe sampler to take 1 mL of sample from step (3) and pass it through a 0.22 μm nylon membrane, and place it in a 2 mL brown injection bottle to which 0.50 mL of methanol has been added in advance. Use an ultra-high performance liquid chromatography triple quadrupole mass spectrometer (UPLC-MS / MS) to determine the concentration of SMR and obtain the effect of Fenton-like degradation of SMR under different system conditions, such as Figure 5 shown.

[0033] 4. Effect of pH value on the degradation performance of Fenton-like system of iron-copper β-cyclodextrin polymer material:

[0034] (1) Take a certain amount of SMR stock solution and ultrapure water and add them into a 250 mL beaker to make the concentration reach the set value. Unless otherwise specified, the initial concentration of SMR is set to 1.00 mg / L;

[0035] (2) Using nitric acid and ammonia water to adjust the pH value of the treated liquid to 3, 4, 5, 6, 7, and 8 respectively;

[0036] (3) In a 250 mL beaker, the initial concentration of SMR was controlled to be 1.00 mg / L, the dosage of Fe-Cu β-cyclodextrin polymer material was 1.20 g / L, the dosage of H2O2 was 40.00 mM, and the total reaction volume was controlled to be 50 mL. The mixture was placed on a digital constant temperature magnetic stirrer at a temperature of 25 °C and a speed of about 500 r / min. The H2O2 addition time was used as the timing zero point, and samples were taken at 5 min, 10 min, 15 min, 20 min, 25 min, and 30 min respectively;

[0037] (4) Use a disposable syringe sampler to take 1 mL of the sample from step (3) and pass it through a 0.22 μm nylon membrane, and place it in a 2 mL brown injection bottle to which 0.50 mL of methanol has been added in advance. Use an ultra-high performance liquid chromatography triple quadrupole mass spectrometer (UPLC-MS / MS) to determine the concentration of SMR, and obtain the effect of the iron-copper β-cyclodextrin polymer material Fenton system on the degradation of SMR under different pH conditions, such as Figure 6 shown.

[0038] 5. Effect of the dosage of iron-copper β-cyclodextrin polymer material on the degradation performance of the Fenton-like system of iron-copper β-cyclodextrin polymer material:

[0039] (1) Take a certain amount of SMR stock solution and ultrapure water and add them into a 250 mL beaker to make the concentration reach the set value. Unless otherwise specified, the initial concentration of SMR is set to 1.00 mg / L;

[0040] (2) Using nitric acid and ammonia water to adjust the pH value of the treated liquid to 3 respectively;

[0041] (3) In a 250 mL beaker, the initial concentration of SMR was controlled to be 1.00 mg / L, the dosage of Fe-Cu β-cyclodextrin polymer was 0.20 g / L, 0.60 g / L, 1.20 g / L, 1.60 g / L, 1.20 g / L, the dosage of H2O2 was 40.00 mM, and the total reaction volume was controlled to be 50 mL. The mixture was placed on a digital constant temperature magnetic stirrer at a temperature of 25 °C and a speed of about 500 r / min for reaction. The H2O2 addition time was used as the timing zero point, and samples were taken at 5 min, 10 min, 15 min, 20 min, 25 min, and 30 min respectively;

[0042] (4) Use a disposable syringe sampler to take 1 mL of the sample from step (3) and pass it through a 0.22 μm nylon membrane, and place it in a 2 mL brown injection bottle to which 0.50 mL of methanol has been added in advance. Use an ultra-high performance liquid chromatography triple quadrupole mass spectrometer (UPLC-MS / MS) to determine the concentration of SMR, and obtain the effect of the iron-copper β-cyclodextrin polymer material Fenton system on the degradation of SMR under different iron-copper β-cyclodextrin polymer material dosage conditions, such as Figure 7 shown.

[0043] 6. Effect of H2O2 dosage on the degradation performance of Fenton-like system of Fe-Cu β-cyclodextrin polymer material:

[0044] (1) Take a certain amount of SMR stock solution and ultrapure water and add them into a 250 mL beaker to make the concentration reach the set value. Unless otherwise specified, the initial concentration of SMR is set to 1 mg / L;

[0045] (2) Using nitric acid and ammonia water to adjust the pH value of the treated liquid to 3 respectively;

[0046] (3) In a 250 mL beaker, the initial concentration of SMR was controlled to be 1.00 mg / L, the dosage of iron-copper β-cyclodextrin polymer was 1.20 g / L, the dosage of H2O2 was 5.00 mM, 10.00 mM, 15.00 mM, 20.00 mM, 30.00 mM, 40.00 mM, and the total reaction volume was controlled to be 50 mL. The mixture was placed on a digital constant temperature magnetic stirrer at a temperature of 25 °C and a speed of about 500 r / min for reaction. The H2O2 addition time was used as the timing zero point, and samples were taken at 5 min, 10 min, 15 min, 20 min, 25 min, and 30 min, respectively;

[0047] (4) Use a disposable syringe sampler to take 1 mL of the sample from step (3) and pass it through a 0.22 μm nylon membrane, and place it in a 2 mL brown injection bottle to which 0.50 mL of methanol has been added in advance. The concentration of SMR is determined using an ultra-high performance liquid chromatography triple quadrupole mass spectrometer (UPLC-MS / MS) to obtain the effect of the iron-copper β-cyclodextrin polymer material Fenton system on the degradation of SMR under different H2O2 dosage conditions, such as Figure 8 shown.

[0048] VII. Effect of temperature on the degradation performance of Fenton-like system of iron-copper β-cyclodextrin polymer material SMR:

[0049] (1) Take a certain amount of SMR stock solution and ultrapure water and add them into a 250 mL beaker to make the concentration reach the set value. Unless otherwise specified, the initial concentration of SMR is set to 1.00 mg / L;

[0050] (2) Using nitric acid and ammonia water to adjust the pH value of the treated liquid to 3 respectively;

[0051] (3) In a 250 mL beaker, the initial concentration of SMR was controlled to be 1.00 mg / L, the dosage of Fe-Cu β-cyclodextrin polymer was 1.20 g / L, the dosage of H2O2 was 10.00 mM, and the total reaction volume was controlled to be 50 mL. The mixture was placed on a digital constant temperature magnetic stirrer at 25 ℃, 35 ℃, and 45 ℃ with a rotation speed of about 500 r / min. The H2O2 addition time was used as the timing zero point, and samples were taken at 5 min, 10 min, 15 min, 20 min, 25 min, and 30 min respectively;

[0052] (4) Use a disposable syringe sampler to take 1 mL of the sample from step (3) and pass it through a 0.22 μm nylon membrane, and place it in a 2 mL brown injection bottle to which 0.50 mL of methanol has been added in advance. Use an ultra-high performance liquid chromatography triple quadrupole mass spectrometer (UPLC-MS / MS) to determine the concentration of SMR, and obtain the effect of the iron-copper β-cyclodextrin polymer material Fenton system on the degradation of SMR under different temperature conditions, such as Fig. 9 shown.

[0053] 8. Effect of rotation speed on the degradation performance of SMR of Fe-Cu β-cyclodextrin polymer material Fenton system:

[0054] (1) Take a certain amount of SMR stock solution and ultrapure water and add them into a 250 mL beaker to make the concentration reach the set value. Unless otherwise specified, the initial concentration of SMR is set to 1.00 mg / L;

[0055] (2) Using nitric acid and ammonia water to adjust the pH value of the treated liquid to 3 respectively;

[0056] (3) In a 250 mL beaker, the initial concentration of SMR was controlled to be 1.00 mg / L, the dosage of Fe-Cu β-cyclodextrin polymer material was 1.20 g / L, the dosage of H2O2 was 10.00 mM, and the total reaction volume was controlled to be 50 mL. The mixture was placed on a digital constant temperature magnetic stirrer at a temperature of 35 °C and a speed of about 300 r / min, 500 r / min, and 700 r / min. The H2O2 addition time was used as the timing zero point, and samples were taken at 5 min, 10 min, 15 min, 20 min, 25 min, and 30 min, respectively;

[0057] (4) Use a disposable syringe sampler to take 1.00 mL of the sample from step (3) and pass it through a 0.22 μm nylon membrane, and place it in a 2 mL brown injection bottle to which 0.50 mL of methanol has been added in advance. Use an ultra-high performance liquid chromatography triple quadrupole mass spectrometer (UPLC-MS / MS) to determine the concentration of SMR, and obtain the effect of the iron-copper β-cyclodextrin polymer material Fenton system on the degradation of SMR under different rotation speed conditions, such as Fig.10 shown.

[0058] IX. Effect of H2O2 dosing method on the degradation performance of Fenton-like system of Fe-Cu β-cyclodextrin polymer material:

[0059] (1) Take a certain amount of SMR stock solution and ultrapure water and add them into a 250 mL beaker to make the concentration reach the set value. Unless otherwise specified, the initial concentration of SMR is set to 1.00 mg / L;

[0060] (2) Using nitric acid and ammonia water to adjust the pH value of the treated liquid to 3 respectively;

[0061] (3) In a 250 mL beaker, the initial concentration of SMR was controlled to be 1.00 mg / L, the dosage of iron-copper β-cyclodextrin polymer material was 1.20 g / L, the dosage of H2O2 was 10.00 mM, and the H2O2 addition method was one-time addition (i.e., the H2O2 was added once at the start of the reaction) and segmented addition (i.e., only 1 / 2 of the H2O2 was added at the start of the reaction, and the remaining 1 / 2 of the H2O2 was added after 15 min). The total reaction volume was controlled to be 50 mL. The reaction was placed on a digital constant temperature magnetic stirrer at a temperature of 35 ℃ and a speed of about 500 r / min. The H2O2 addition time was used as the timing zero point, and samples were taken at 5 min, 10 min, 15 min, 20 min, 25 min, and 30 min respectively;

[0062] (4) Use a disposable syringe sampler to take 1 mL of the sample from step (3) and pass it through a 0.22 μm nylon membrane, and place it in a 2 mL brown injection bottle to which 0.50 mL of methanol has been added in advance. The concentration of SMR is determined using an ultra-high performance liquid chromatography triple quadrupole mass spectrometer (UPLC-MS / MS) to obtain the effect of the iron-copper β-cyclodextrin polymer material Fenton system on the degradation of SMR under different H2O2 addition conditions, such as Fig.11 shown.

[0063] The above studies on infrared spectrum analysis, scanning electron microscopy analysis, X-ray diffraction analysis, X-ray energy spectrum analysis and specific surface area analysis of the iron-copper β-cyclodextrin polymer material before and after the reaction have shown that the iron-copper β-cyclodextrin polymer material has great potential to replace the traditional Fenton reagent. As a Fenton-like catalyst, it can efficiently catalyze and activate H2O2 to produce hydroxyl radicals, which attack sulfonamide antibiotics, thereby achieving the purpose of degrading trace sulfonamide antibiotics in water.

Claims

1. An iron-copper β-cyclodextrin polymer material for efficient activation of H2O2, characterized in that: The specific steps of the preparation method are as follows: (1) esterification reaction of monohydrated citric acid and β-cyclodextrin is carried out under the catalysis of potassium dihydrogen phosphate to prepare citric acid cross-linked β-cyclodextrin polymer; (2) Stir the mixture in a water bath and add ferrous sulfate and copper nitrate and stir for 15 minutes. When the substances in the mixed solution are completely dissolved and the solution is clear, seal the beaker with laboratory tin foil. (3) placing the sealed beaker in step (2) in a digital display air drying oven to dry, thereby obtaining a brown solid product, iron-copper β-cyclodextrin material; (4) The brown solid obtained in step (3) is cooled to room temperature, filtered with 500 mL of ultrapure water for multiple times to remove impurities, dried in a vacuum drying oven, and taken out and ground to obtain the desired iron-copper β-cyclodextrin polymer material, denoted as CACD-Fe-Cu, which is placed in a desiccator for storage for later use.

2. The preparation method according to claim 1, characterized in that: In the esterification reaction, β-cyclodextrin and citric acid monohydrate were placed in a 500 mL beaker according to a mass ratio (mβ-CD:mCA=2:1), and 1.50 g of potassium dihydrogen phosphate and 135 mL of ultrapure water were added and mixed evenly.

3. The preparation method according to claim 1, characterized in that: In the iron-copper β-cyclodextrin polymerization reaction, step (1) is placed in a 90°C water bath stirring pot and stirred for 15 min. After stirring for 5 min, ferrous sulfate and copper nitrate in a mass ratio of (mFeSO4:mCu(NO3)2=3:1) are added and stirring is continued for 10 min.

4. The preparation method according to claim 1, characterized in that: The temperature of the digital display air drying oven in step (3) is 135-145°C, and the reaction time is 3.5-4.5 h.

5. The preparation method according to claim 1, characterized in that: In step (4), the temperature of the vacuum drying oven is 60°C and the drying time is 12 hours.

6. An iron-copper β-cyclodextrin polymer material for efficient activation of H2O2, characterized in that: The iron-copper β-cyclodextrin polymer material is prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the iron-copper β-cyclodextrin polymer material as claimed in claim 6 in activated H2O2 advanced oxidation technology, characterized in that: As a Fenton-like catalyst, CACD-Fe-Cu can efficiently catalyze and activate H2O2 to produce hydroxyl radicals, which attack sulfonamide antibiotics, thereby achieving the purpose of degrading trace sulfonamide antibiotics in water.

Citation Information

Patent Citations

  • Preparation method and application of cyclodextrin-coated iron-copper bimetallic nano material

    CN115254109A

  • Synergistic oxidation-reduction agent for polluted groundwater remediation

    CN116589069A

Cited By

  • Fenton reagent, polishing solution, polishing method of diamond substrate, and polished diamond wafer

    CN120290108A

  • Fenton reagent, polishing solution, polishing method of diamond substrate, and polished diamond wafer

    CN122278357A